The Effect of Automated Written Corrective Feedback (AWCF) on Students’ Writing at SMP 47 Pekanbaru - Helfianora Ofrita; Alfina Darmis; Rosmanizar Rosmanizar (Jurnal Pendidikan Tuntas, 2023)
Nowadays, English is one of the languages that must be mastered, especially for students. One of the skills that must be mastered by students is writing. However, students have some problems in writing, such as a lack of ideas and creativity in writing, lack of motivation in writing, and there are still many grammatical errors in writing. To overcome this problem, researchers used Grammarly as a treatment to provide feedback on students' writing. Therefore, this study aims to determine whether Automated Written Corrective Feedback using Grammarly significantly affects Students' Writing Ability at SMP Negeri 47 Pekanbaru. The type of research used in this research is the pre-test-post-test group quasi-experimental design. This research involved tenth-grade students of SMP Negeri 47 Pekanbaru Kota. The sampling technique used is purposive sampling. The number of samples in this study amounted to 74 people divided into two classes, namely 37 people from class IX 9 as the experimental class and 37 from class IX 10 as the control class. The data collected in this study were analyzed using the t-test. Based on the results of statistical calculations, the t-table value is 1.666, and the t-count value is 2.192, which shows that the t-value is greater than the t-table (2.192 > 1.674). Furthermore, based on independent sample t-test on p-value or sig. (2-tailed) is 0.005. These results reject the null hypothesis (H0), and the alternative hypothesis (Ha) is accepted. It concluded that using Grammarly as Automated Written Corrective Feedback has a significant effect on students writing skills of tenth-grade students at SMP 47 Pekanbaru Keyword: Writing Skill, Quasi Experimental, Automated Writing Corrective Feedback, Grammarly